Compiled Ordinances: Town of Albuquerque 81 (William C. Heacock ed., 1887) - (:unkn) unknown (My University, 1887)
Chapter 21-Deadly Weapon, § 1: It shall be unlawful for any person to carry a deadly weapon, either concealed or unconcealed, within the limits of the town of Albuquerque, unless the same be carried in lawful defense of himself, his family or his property, the same being at the time threatened with danger, or unless by order of legal authority, or unless such person be a regularly authorized officer of the law in the discharge of his official duty.
Keywords: CARRY